Кондитерська галузь України. Напрямки підвищення її конкурентоспроможності - Горбунов, Микола Петрович; Погорєлов, Сергій Миколайович; Бурава, Сергій (НТУ"ХПІ", 2016)
У статті надано аналіз сучасного стану ринку кондитерської галузі, зроблено аналіз факторів, які вплинули на його загальне погіршання, з’ясовано зовнішні чинники впливу на конкурентоспроможність підприємств та продукції кондитерської галузі, запропоновано заходи з підвищення їх конкурентоспроможності.

In this article current state of the confectionery industry and factors of its overall decline were analyzed; external factors that influence competitiveness of confectionery industry’s enterprises and their products were defined; measures to improve their competitiveness were proposed. The problem of competitiveness of the enterprise products is not new, it remains to be a difficult and inevitable part of our lives. This problem is especially relevant today, when Ukrainian enterprises regardless of their form of organization and the ownership of their products come out on the inside especially on foreign markets.
Confectionery industry of Ukraine. Directions of increase of its competitiveness
Keywords: внутрішні ринки; зовнішні ринки; кондитерські підприємства; кондитерська продукція; конкурентна боротьба; експорт; торгівельні преференції; стратегії; confectionery industry; competitiveness; external factors